2014
DOI: 10.1364/ao.53.007819
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ultraviolet-curable adhesive bottle-like microresonators by wetting and photocuring

Abstract: This work presents a remarkably simple method for the fabrication of ultraviolet (UV)-curable adhesive bottle-like microresonators (BLMRs). The main fabrication process involves two steps: (1) creating liquid bottle-like microcavities along the taper waist of an optical fiber taper under interfacial tension and (2) curing the liquids into solids by UV light irradiation. The shape of the BLMRs can be fitted with a truncated harmonic-oscillator profile. Whispering gallery mode resonances of the bottle-like micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…f C , f P and f H ; ω C , ω P , ω H are respectively the focal points and beam widths of the generated PNJs from these three profiled R-MPCMs. Choice of P-type and H-type profiles, as optimization options, is mainly due to the consideration of developing three-dimensional (3D) high- Ri superlens with controllable heating-and-deforming or self-assembling methods in the future 2527 .
Figure 4( a ) Four boundary profiles for narrowing the transverse beam widths of the PNJs. C-type: circular type, P-type: parabolic type, H-type: harmonic-oscillating type, L-type: linear type.
…”
Section: Resultsmentioning
confidence: 99%
“…f C , f P and f H ; ω C , ω P , ω H are respectively the focal points and beam widths of the generated PNJs from these three profiled R-MPCMs. Choice of P-type and H-type profiles, as optimization options, is mainly due to the consideration of developing three-dimensional (3D) high- Ri superlens with controllable heating-and-deforming or self-assembling methods in the future 2527 .
Figure 4( a ) Four boundary profiles for narrowing the transverse beam widths of the PNJs. C-type: circular type, P-type: parabolic type, H-type: harmonic-oscillating type, L-type: linear type.
…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Gu and others proposed to use UV curing binder to prepare microcavity resonators. The preparation method was simple, cheap and sensitive, which provided great potential for UV‐curable adhesives . In the same year, Zhang et al.…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 99%
“…It has been shown that ultraviolet (UV)-curing epoxy can be used to form droplets on an optical fiber that, thanks to interfacial forces, self-assemble into microbottles [22]. These resonators showed Q -factors near 105, and a strong dependence of the resonance wavelengths on the power used to probe them (due to the large thermo-optic coefficient of the resin).…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…( a ) Epoxy-based microbottle. Image adapted with permission from [22] (©the Optical Society of America); ( b ) “soften-and-compress” method. Image adapted with permission from [21] (©the Optical Society of America); ( c ) spin-on-glass-based microbottle, image adapted from [23], released under the CC BY 4.0 license (); ( d ) “heat-and-pull” method.…”
Section: Figurementioning
confidence: 99%